Analysis of Service Policy For Pregnant Mothers, Partnership, Nifas, New Birth and KB During The Covid-19 Pandemic At The Community Health Center Tanjung Haloban - Tampubolon, Elmina (Universitas Aisyah Pringsewu, 2022)
The rules imposed during the COVID-19 pandemic are considered to have a direct impact on health services. One of the regulations is considered to have a negative impact on the implementation of the KIA program. This is a qualitative study with an observational method, which aims to generate or explore in-depth descriptive data regarding Service Policies for Pregnant Women, Maternity, Postpartum, Newborns and Family Planning During the Covid 19 Pandemic at Pusat Kesehatan Masyarakat Tanjung Haloban. The research period starts from December 2021 to March 2022. The research informants are 6 informants consisting of: Head of Pusat Kesehatan Masyarakat, the Coordinator Midwife, the Implementer of MCH and Family Planning Programs, Multigravida Pregnant Women, Multigravida Maternity and Postpartum Mothers and PUS. Only coordinating midwives have received training, pregnant women are reluctant to visit the Pusat Kesehatan Masyarakat Tanjung Haloban due to concerns about being infected with the Covid-19 virus, there is a lack of infrastructure for the implementation of quarantine for pregnant women, HIV test packages are not available for pregnant women, family planning services for PUS carried out as before the Pandemic with additional application of health protocols, pregnant women services, namely Antenatal Care services carried out as usual with additional screening in the form of vaccination activities for pregnant women and Covid-19 examinations, there was no reduction in the KIA/KB service program provided at the Pusat Kesehatan Masyarakat Tanjung Haloban at pandemic. KIA services experienced a decline and did not reach the SPM target, while KB services experienced an increase in participants and reached the SPM target. It is necessary to make proposals for the procurement of HIV test kits, re-propose additional quarantine rooms for pregnant women, provide education regarding delivery service procedures during the pandemic, and planning related to the home visit program for pregnant women services.Abstrak: Aturan-aturan yang diberlakukan dimasa Pandemi COVID-19 dinilai berdampak secara langsung pada layanan kesehatan. Salah satu aturan yang dinilai berdampak negatif pada pelaksanaan program KIA. Ini adalah penelitian kualitatif dengan metode observasional, yang bertujuan untuk menghasilkan atau menggali data deskriftif secara mendalam mengenai Kebijakan Pelayanan Pada Ibu Hamil, Bersalin, Nifas, Bayi Baru Lahir Serta KB Pada Masa Pandemi Covid 19 di Pusat Kesehatan Masyarakat Tanjung Haloban. Waktu penelitian dimulai dari bulan Desember 2021 sampai Maret 2022. Informan penelitian sebanyak 6 orang informan yang terdiri dari : Kepala Pusat Kesehatan Masyarakat, Bidan Koordinator, Pelaksana Program KIA dan KB, Ibu Hamil multigravida, Ibu Bersalin dan Nifas multigravida dan Pasangan Usia Subur. Hanya bidan koordinator yang sudah pernah mendapatkan pelatihan, Ibu hamil enggan melakukan kunjungan ke Pusat Kesehatan Masyarakat Tanjung Haloban akibat kekhawatiran terinfeksi virus Covid-19, ada kekurangan prasarana ruangan pelaksanaan karantina ibu hamil, tidak tersedia paket tes HIV untuk ibu hamil, pelayanan KB pada Pasangan Usia Subur dilakukan seperti sebelum Pandemi dengan tambahan penerapan protokol kesehatan, pelayanan Ibu Hamil yaitu pelayanan Antenatal Care dilakukan seperti biasa dengan tambahan skrinning berupa kegiatan vaksinasi pada ibu hamil dan pemeriksaan Covid-19, tidak ada pengurangan program layanan KIA/KB yang diberikan di Pusat Kesehatan Masyarakat Tanjung Haloban dimasa Pandemi Covid-19, Layanan KIA mengalami penurunan dan tidak mencapai target SPM, sedangkan Layanan KB mengalami peningkatan peserta KB aktif dan mencapai target SPM. Perlu dilakukan pengusulan untuk pengadaan alat tes HIV, pengusulan ulang penambahan ruangan karantina bagi ibu hamil, edukasi tetang prosedur pelayanan persalinan dimasa Pandemi, perencanaan terkait program kunjungan lapangan (home visit) pada Pelayanan Ibu hamil.